Applications of Taguchi method for optimization of dye solar cell design - Oktiawati, U.Y. (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper addresses the optimal Dye Solar Cell (DSC) design considering parameters namely TiO2 thickness, surface area, iodide concentration in electrolyte and TiO2 passivation layer thickness as they have influence on DSC performance. It aims to do the research of the practical use of Taguchi method in the optimization of DSC design in order to improve the performance of DSC. This work highlight on the integration of Taguchi method with simulation which showed that the optimal design of DSC is 10 μm thickness of TiO2, 90m2/g of TiO2 photoelectrode surface area, 1 M iodide concentration in electrolyte and two layers with 20 nm thickness of TiO2 passivation layer with efficiency of 4.59165. All the features of the Taguchi-based optimization were also discussed. © 2017, Penerbit Universiti Kebangsaan Malaysia. All rights reserved.